Contrasts between the specialized and unprofessional literature critics: the booktubers and the discourses about the book and the reading - Vizibeli, Danilo (2016)
This paper aims at describing, based on the French Discourse Analysis and Cultural History, the discursive practices of contemporary representation of the reader through some reflections on the specialized and amateur critics. It is used as corpus cut one piece of news published on the entertainment portal UOL, under the title "Literary Market: will the booktubers replace the specialized critics?", signed by Rodrigo Casarin. It seeks to list and understand the discursive formations of the general reader and the professional player, this understood as the professional literary criticism that serves as an institutionalized reading. It wonders: why is the formal literary criticism of prestige, but when you want to sell the works and move the publishing market, it is necessary, at present, to promote the amateur comment? What are the limits between the general reader and the expert critical? Why does posting a video on the Internet give social capital to the one that is called a voracious reader and bring together readers and writers? In terms of language, what is said about reading at the time of cyberculture? To account for these reflections, theoretical reflections found in the works of Orlandi (2012), Foucault (2010) and Chartier (1998, 2010) are used.